Search for charged Higgs bosons produced in vector boson fusion processes and decaying into vector boson pairs in proton-proton collisions at √s=13TeV; European Physical Journal C; Vol. 81, iss. 8 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen